Anxiety, Depression, and the Interpersonal Theory of Suicide in a Community Sample of Adults with Autism Spectrum Disorder. Issue 2 (3rd April 2021) - Dow, Deanna; Morgan, Lindee; Hooker, Jessica L.; Michaels, Matthew S.; Joiner, Thomas E.; Woods, Juliann; Wetherby, Amy M.
Abstract : The present study examines occurrence of depression, anxiety, and suicidality in adults with autism spectrum disorder (ASD), relationships between social difficulties and mental health, and application of the Interpersonal Theory of Suicide in this population. Ninety-eight adults with ASD completed an online survey. Data were analyzed using bivariate correlations, independent samples t-tests, and simple mediational analyses. A substantial proportion reported a lifetime history of anxiety (63%), depression (55%), and suicide attempts (19%), as well as recent suicidal ideation (12%). Social difficulty was associated with higher psychiatric concerns. Thwarted belongingness and perceived burdensomeness were associated with social dissatisfaction, current suicidal ideation, and history of depression. Results suggest the need for widespread screening and intervention services for co-occurring psychiatric conditions in this population.